Jews in Early Christian Law: Byzantium and the Latin West, 6th-11th Centuries - Tolan, John; Foschia, Laurence; de Lange, Nicholas; Nemo-Pekelman, Capucine (Jews in Early Christian Law: Byzantium and the Latin West, 6th-11th Centuries, 2014)
What is the place of Jews in medieval Christian societies? in the ninetheenth and early twentieth centuries, this question was largely confined to Jewish scholars, and the academic debates where inseparable from the upheavels of the lives of contemporary European Jews.